2020
DOI: 10.1016/j.meegid.2020.104474
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the proteome of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) for cell-penetrating peptides involved in pathogenesis or applicable as drug delivery vectors

Abstract: Synthetic or natural derived cell-penetrating peptides (CPPs) are vastly investigated as tools for the intracellular delivery of membrane-impermeable molecules. As viruses are intracellular obligate parasites, viral originated CPPs have been considered as suitable intracellular shuttling vectors for cargo transportation. A total of 310 CPPs were identified in the proteome of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Screening the proteome of the cause of COVID-19 reveals that SARS-CoV-2 CPP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 143 publications
0
18
0
Order By: Relevance
“…In this respect, SARS-CoV2 virus, the etiological causative of COVID-19, needs to infect animals or humans to replicate, as other viruses, and as a consequence it should have CCPs in its proteome. A recent computational study analyzed the SARS-CoV-2 proteins and identified >300 sequences with potential CPP ability and involved in important processes like protein–protein interactions and homo/hetero-oligomer stabilization [ 82 ]. Further filtering allowed the identification of peptide sequences with no antigenic or allergenic properties and resistant to main groups of proteases.…”
Section: Main Methodologies To Cyclic and Macrocyclic Peptidesmentioning
confidence: 99%
“…In this respect, SARS-CoV2 virus, the etiological causative of COVID-19, needs to infect animals or humans to replicate, as other viruses, and as a consequence it should have CCPs in its proteome. A recent computational study analyzed the SARS-CoV-2 proteins and identified >300 sequences with potential CPP ability and involved in important processes like protein–protein interactions and homo/hetero-oligomer stabilization [ 82 ]. Further filtering allowed the identification of peptide sequences with no antigenic or allergenic properties and resistant to main groups of proteases.…”
Section: Main Methodologies To Cyclic and Macrocyclic Peptidesmentioning
confidence: 99%
“…Lately, in an interesting study, screening the proteome of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) disclosed a total of 310 CPPs. Whereas 64% of these CPPs had immuno-modulatory attributes, 22% were identified with anti-cancer properties [ 8 ]. Experimentally, CPPs have demonstrated to be able to deliver small and large bioactive cargos into cells both in vitro and in vivo [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 3-chymotrypsin-like viral protease (3CL pro ) is the main protease of SARS-CoV-2 in charge of cleaving the polyproteins into individual functional components (Hilgenfeld 2014). The 3CL pro operates on at least eleven cleavage sites on the larger polyprotein resulting in non-structural proteins 4-16 (Hemmati et al 2020). These non-structural proteins will later assemble into a replication transcription complex crucial to viral replication (Yang et al 2003).…”
Section: Introductionmentioning
confidence: 99%